Electrical and Dielectric Characterization of Bi12GeO20 Prepared by Modified Pechini Method - C. G. P. Moraes; F. A. A. Jesus; Z. S. Macedo (Advances in Condensed Matter Physics)
Bismuth germanate (Bi12GeO20) ceramics were produced using modified Pechini route, and the synthesis parameters, crystalline phases, microstructure, and sintering conditions were investigated. Bi12GeO20 powders with submicrometric particle sizes were investigated for calcination temperatures from 400 to 600°C, with soaking times of 1 h and 5 h. Controlling the synthesis parameters, dense ceramics with two different grain sizes of 3.4 ± 0.5 µm and 5.7 ± 0.8 µm could be produced after sintering at 750°C/1 h. The electric and dielectric properties of these ceramics were determined by impedance spectroscopy (IS). From the results, it was concluded that the dielectric permittivity measured at high frequencies is insensitive to the grain size, while the AC dark conductivity presents a noticeable dependency on this feature. This behaviour was discussed on the basis of a Maxwell-Wagner interfacial relaxation, whose intensity depends directly on the volume fraction of grain boundaries in the sample.